Toner additive particles, toner, and two-component developer

Incorporating polyrotaxane into external additive particles for toners addresses the issue of image density fluctuations in low-humidity environments by facilitating charge movement, enhancing image stability and quality.

JP7612494B2Active Publication Date: 2025-01-14CANON KK
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021069800
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-16
Publication Date
2025-01-14
Estimated Expiration
2041-04-16

AI Technical Summary

Technical Problem

Existing toners experience significant changes in image density in low-humidity environments due to excessive charging, leading to decreased image quality and defects.

Method used

Incorporation of polyrotaxane, a material with high molecular mobility, into external additive particles for toners to facilitate charge movement and reduce excessive charging, thereby stabilizing image density.

Benefits of technology

The use of polyrotaxane in external additive particles maintains consistent image density in low-humidity environments, reducing the likelihood of image defects and ensuring high-quality output over extended periods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612494000001
    Figure 0007612494000001
Patent Text Reader

Abstract

To provide an external additive particle for toner with which a toner reducing a change in image density is obtained even when continuous image output is performed in a low humidity environment.SOLUTION: An external additive particle for toner includes resin. The resin includes a first resin and a second resin different from the first resin. The first resin is polyrotaxane. The polyrotaxane has (i) a plurality of cyclic molecules and (ii) chain molecules included in rings of the cyclic molecules in a skewer shape, and (iii) the chain molecules have two or more blocking groups for preventing the cyclic molecules from being eliminated from the chain molecules.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an external toner additive particle, a toner, and a two-component developer. [Background technology]

[0002] External additives are widely used in toners used in electrophotographic image forming apparatuses, and silica fine particles, resin fine particles, and the like are known as external additives.

[0003] Furthermore, in order to obtain high-quality images, the performance required of a toner additive is to improve the toner's electrostatic chargeability, fluidity, etc. For example, Patent Document 1 discloses that by using resin particles surface-treated with silicone oil as an external additive for a toner, the toner has excellent electrostatic chargeability and can sustain the output of high-quality images without the occurrence of abnormal images for a long period of time. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-175964 A [Patent Document 2] WO01 / 083566 [Patent Document 3] JP 2017-31258 A Summary of the Invention [Problem to be solved by the invention]

[0005] One aspect of the present disclosure is to provide an external toner additive particle that can provide a toner having an image density that is unlikely to change even when images are continuously output in a low-humidity environment.

[0006] Another aspect of the present disclosure is directed to providing a toner having the external toner additive particles according to the present disclosure.

[0007] Another aspect of the present disclosure is directed to providing a two-component developer having the toner additive particles according to the present disclosure. [Means for solving the problem]

[0008] According to one aspect of the present disclosure, there is provided a toner additive particle comprising a resin, The resin includes a first resin and a second resin different from the first resin, the first resin is a polyrotaxane; The polyrotaxane is (i) a plurality of cyclic molecules; (ii) a chain molecule that is pierced and included in the ring of the cyclic molecule; having (iii) the chain molecule has two or more blocking groups that prevent the cyclic molecule from being detached from the chain molecule; The present invention provides an external toner additive particle comprising:

[0009] According to another aspect of the present disclosure, there is provided a toner comprising toner particles and an external additive on the surfaces of the toner particles, The toner is provided in which the external additive is the external toner additive particles according to the present disclosure.

[0010] According to another aspect of the present disclosure, there is provided a two-component developer containing a toner and a magnetic carrier, A two-component developer is provided in which the toner is a toner of the present disclosure. Effect of the Invention

[0011] According to one aspect of the present disclosure, there can be provided an external toner additive particle that can provide a toner in which image density is unlikely to change even when images are continuously output in a low-humidity environment.

[0012] According to another aspect of the present disclosure, a toner having the external toner additive particles according to the present disclosure can be provided.

[0013] According to another aspect of the present disclosure, there is provided a two-component developer having the toner additive particles according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] In this disclosure, the expressions "xx or more and xx or less" and "xx to xx" expressing a numerical range mean a numerical range including the endpoints, that is, the lower limit and the upper limit, unless otherwise specified.

[0015] <Background to the invention> In recent years, image forming apparatuses are required to be less susceptible to image defects even in harsh environments. One example of this is that in low-humidity environments where toner is likely to be overcharged, the density of the formed image is likely to decrease, and the present inventors believe that there is still room for improvement.

[0016] In response to this, the present inventors considered it necessary to study a technology that can prevent image density reduction in a low humidity environment by improving external additive particles, which are materials widely used in toners. As general external additive particles, inorganic particles such as silica fine particles and resin particles are known, but compared with inorganic particles, resin particles are easy to design by using the monomer composition of the resin or additives, and are likely to become external additive particles that can obtain desired toner physical properties.

[0017] Based on the above-mentioned idea, the present inventors have investigated the incorporation of various materials into resin-containing particles in order to obtain external additive particles that can produce toners that are less likely to reduce image density even in low-humidity environments. As a result of extensive investigations, they have found that incorporation of polyrotaxane into resin-containing particles is effective in realizing external additive particles having the above-mentioned properties.

[0018] Since the cyclic molecules contained in the polyrotaxane can rotate and move along the chain molecules, the polyrotaxane is a material with high molecular mobility. The inventors believe that by including such a material with high molecular mobility in the external additive particles, the charge in the external additive particles can be easily moved, and this makes it easier for excess charge generated in the toner to escape via the external additive particles. As a result, the inventors speculate that the toner is less likely to be excessively charged even in a low humidity environment, and the image density is less likely to decrease.

[0019] <First resin> The first resin according to the present disclosure is a resin having a polyrotaxane structure in its molecule (hereinafter, also referred to as "polyrotaxane"). The polyrotaxane structure refers to a structure having (i) a plurality of cyclic molecules, (ii) linear molecules that are skewered and included in the rings of the cyclic molecules, and (iii) the linear molecules have two or more blocking groups that prevent the cyclic molecules from being detached from the linear molecules.

[0020] Generally, a molecular assembly in which a chain molecule penetrates the inside of the ring of a cyclic molecule and a bulky molecule is bonded to the end of the axis, binding the cyclic molecule to the chain molecule, is called a rotaxane. A molecular assembly in which many cyclic molecules are linked to one chain molecule is called a polyrotaxane. The cyclic molecule is not bonded to the chain molecule, and can rotate and move on the chain molecule.

[0021] The polyrotaxane of the present disclosure can be produced by a known method, for example, the method described in Patent Document 2 or Patent Document 3, or can be obtained and used as a commercially available product (product name: CELME Super Polymer, manufactured by ASM Co., Ltd.). The polyrotaxane according to the present disclosure may be used alone or in combination of two or more types.

[0022] In addition, the content of the first resin (polyrotaxane) is preferably 0.1% by mass or more and 30.0% by mass or less with respect to the mass of the toner external additive particles. The content is more preferably 1.0% by mass or more, and more preferably 2.0% by mass or more. It is more preferably 15.0% by mass or less, and even more preferably 10.0% by mass or less. It has been found that when the content of polyrotaxane is 0.2% by mass or more, the image density in a low humidity environment is less likely to decrease. In addition, when the content of polyrotaxane is 30.0% by mass or less, it is considered that the charge accumulated in the toner is less likely to be excessively relaxed, and it has been found that image fogging is less likely to occur in a high temperature and high humidity environment.

[0023] In the polyrotaxane of the present disclosure, the number of cyclic molecules threaded into one linear molecule (the inclusion amount) is not particularly limited. The inclusion amount can be controlled by the molar ratio of the linear molecule and the cyclic molecule used in producing the polyrotaxane.

[0024] <Cyclic molecules> The cyclic molecules contained in the polyrotaxane are not particularly limited as long as they are capable of including chain molecules and have a ring structure through which the chain molecules can penetrate in a skewered manner.

[0025] Examples of the cyclic molecule of the present disclosure include cyclodextrins, crown ethers, benzocrowns, dibenzocrowns, dicyclohexanocrowns, and derivatives or modified forms thereof. Among these, cyclodextrins are preferred because they are easy to include chain molecules. That is, the cyclic molecule is preferably a molecule having a cyclodextrin skeleton. More preferably, the cyclic molecule is a molecule having at least one cyclodextrin skeleton selected from the group consisting of an α-cyclodextrin skeleton, a β-cyclodextrin skeleton, and a γ-cyclodextrin skeleton. The cyclic molecule may be one type, or two or more types may be used in combination.

[0026] In the present disclosure, a molecule having a cyclodextrin skeleton is regarded as a cyclodextrin molecule, or a molecule having a structure synthesized when a derivatization reaction is performed on a hydroxyl group of a cyclodextrin molecule.

[0027] <Side chains attached to cyclodextrin> It is preferable that the cyclic molecule of the polyrotaxane is a molecule having a cyclodextrin skeleton, and the molecule having the cyclodextrin skeleton has cyclodextrin and a side chain bonded to the cyclodextrin. Here, the side chain bonded to the cyclodextrin in the present disclosure is treated as a partial structure introduced when a derivatization reaction is performed on a hydroxy group of the cyclodextrin. The side chain may be a linear structure or a branched structure.

[0028] It is believed that the above-mentioned side chains tend to increase the affinity between the polyrotaxane and the resin component. As a result, it is believed that the polyrotaxane is less likely to be present in a biased state and is more likely to be contained in a uniformly dispersed state, which is preferable. In addition, it is preferable that the side chains have a polymer structure, and more preferably a polyester structure or a vinyl polymer structure. Examples of the polyester structure include a polymer structure in which a diol and a dicarboxylic acid are condensed, and a polycaprolactone structure. In addition, the vinyl polymer structure is a polymer structure in which a vinyl monomer is polymerized, and examples thereof include a styrene-methyl methacrylate polymer structure.

[0029] The weight average molecular weight of the molecule having the above-mentioned side chain and cyclodextrin skeleton is preferably 1000 to 50000. It has been found that the amount of transfer residual toner is less likely to become excessive by being in this range. The present inventors speculate that this is because the elasticity of the external additive particles is easily increased due to the entanglement of the polymer structure and the resin component in the polyrotaxane, making it difficult for the external additive particles to be embedded in the toner particles. The weight average molecular weight is more preferably 2500 or more, and even more preferably 7000 or more. Also, it is more preferably 30000 or less, more preferably 20000 or less, and even more preferably 10000 or less.

[0030] A molecule having a cyclodextrin skeleton that satisfies the above weight-average molecular weight can be produced by binding a polymer to cyclodextrin. For example, it can be produced by introducing a polyester structure into the hydroxyl group of cyclodextrin. It can also be produced by a vinyl polymerization reaction between a cyclodextrin derivative having a vinyl-polymerizable double bond and a vinyl monomer.

[0031] The molecular weight of the cyclic molecule can be measured by an analytical device such as GPC after isolating the cyclic molecule. In order to isolate the cyclic molecule, it is necessary to remove the terminal blocking group of the polyrotaxane as a first step. For example, in the case of a polyrotaxane having a terminal blocking group bonded with an amide group or a carbonyl group, a method of heating under acid or base conditions and hydrolyzing the polyrotaxane can be mentioned. Then, the cyclic molecule can be isolated by a conventional method such as reprecipitation, filtration, centrifugation, or membrane separation. The molecular weight of a chain molecule can also be measured by a similar method.

[0032] <chain molecule> The chain molecule of the polyrotaxane is not particularly limited as long as it can pierce the cyclic molecule in a skewered manner, is included in the cyclic molecule, and allows the cyclic molecule to freely rotate, slide, or move. In addition, the chain molecule is preferably a linear molecule. In the present disclosure, a linear molecule is considered to be a molecule having no branch in the main chain of the molecule.

[0033] The chain molecule is preferably at least one selected from the group consisting of polyalkylenes, polyesters, polyethers, polyamides, and polyacrylics, and among these, polyethers are more preferable. That is, the chain molecule is preferably a molecule having a polyether chain. More preferably, it is a molecule having a polyalkylene glycol chain, and even more preferably, it is a molecule having a polyethylene glycol chain.

[0034] <Blocking group> The chain molecule has two or more blocking groups at both ends thereof to prevent the cyclic molecule from being released. The blocking groups of the polyrotaxane can be used without any particular limitation as long as they can prevent the cyclic molecule from being released. Examples of the blocking groups according to the present disclosure include bulky groups for physically preventing the cyclic molecule from being released, and ionic groups for electrically preventing the cyclic molecule from being released. Specific examples of the blocking groups include dinitrophenyl groups, cyclodextrins, adamantyl groups, trityl groups, fluoresceins, and pyrenes, and may be derivatives or modified forms of these.

[0035] <Bonded polyrotaxane> Alternatively, the cyclic molecules of two or more polyrotaxanes may be bonded to each other by forming a chemical bond between each other.

[0036] That is, the polyrotaxane includes a first polyrotaxane and a second polyrotaxane, the polyrotaxane includes a bound polyrotaxane formed by binding the first polyrotaxane and the second polyrotaxane, and the first polyrotaxane and the second polyrotaxane may be bound by a chemical bond between a cyclic molecule carried by the first polyrotaxane and a cyclic molecule carried by the second polyrotaxane.

[0037] Furthermore, a plurality of cyclic molecules contained in one polyrotaxane may be bonded to each other by forming a chemical bond.

[0038] In the present disclosure, a chemical bond may be a single bond or a bond via various atoms or molecules (eg, a bond via a linking group).

[0039] The above-mentioned linked polyrotaxane can be obtained, for example, by reacting a cyclic molecule having a hydroxyl group, such as cyclodextrin, with 1,4-butanediol diglycidyl ether.

[0040] <Particle size of external additive particles> The particle diameter of the toner external additive particles is preferably 50 nm or more and 300 nm or less. If it is 50 nm or more, the spacer effect can be sufficiently exhibited, and if it is 300 nm or less, the amount of transfer residual toner is easily reduced. More preferably, it is 200 nm or less.

[0041] <Second resin> The second resin according to the present disclosure is different from the first resin (polyrotaxane) in that it does not have a polyrotaxane structure in its molecule. The content of the second resin in the toner external additive particles is preferably 70.0 to 99.9% by mass. It is more preferably 85.0% by mass or more, and more preferably 90.0% by mass or more. It is more preferably 99.0% by mass or less, and more preferably 98.0% by mass or less.

[0042] The second resin is not particularly limited, and known thermoplastic resins and thermosetting resins can be used, and one type may be used alone or multiple types may be used in combination. In addition, a thermoplastic resin is preferable because it is thought that it is unlikely to interfere with the molecular motion of polyrotaxane.

[0043] Examples of thermoplastic resins include the following: polystyrene, polymethyl methacrylate, styrene-acrylic acid ester copolymer, styrene-methacrylic acid ester copolymer, styrene-butadiene copolymer, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinyl acetate, polyvinylidene fluoride resin, fluorocarbon resin, perfluorocarbon resin, solvent-soluble perfluorocarbon resin, polyvinylpyrrolidone, petroleum resin, novolac resin, saturated alkyl polyester resin, aromatic polyester resin such as polyethylene terephthalate, polybutylene terephthalate, and polyarylate, polyamide resin, polyacetal resin, polycarbonate resin, polyethersulfone resin, polysulfone resin, polyphenylene sulfide resin, and polyether ketone resin.

[0044] Among these, from the viewpoint of electrostatic charge property and durability, preferred as the resin component are styrene-acrylic acid ester copolymers and / or styrene-methacrylic acid ester copolymers.

[0045] Examples of thermosetting resins include the following: phenol resins, modified phenol resins, maleic resins, alkyd resins, epoxy resins, acrylic resins, unsaturated polyesters obtained by polycondensation of maleic anhydride, terephthalic acid, and polyhydric alcohols, urea resins, melamine resins, urea-melamine resins, xylene resins, toluene resins, guanamine resins, melamine-guanamine resins, acetoguanamine resins, glyptal resins, furan resins, silicone resins, polyimides, polyamideimide resins, polyetherimide resins, and polyurethane resins.

[0046] <Toner and toner particles> The toner according to the present disclosure preferably has toner particles. In the present disclosure, the configurations of the toner and toner particles are described below.

[0047] <Binding resin> The toner particles preferably contain a binder resin. Examples of the binder resin used in the toner particles include the following polymers.

[0048] Homopolymers of styrene and its substituted derivatives, such as polystyrene, poly-p-chlorostyrene, and polyvinyltoluene; Styrenic copolymers such as styrene-p-chlorostyrene copolymer, styrene-vinyltoluene copolymer, styrene-vinylnaphthalene copolymer, styrene-acrylic acid ester copolymer, styrene-methacrylic acid ester copolymer, styrene-α-chloromethyl methacrylate copolymer, styrene-acrylonitrile copolymer, styrene-vinyl methyl ether copolymer, styrene-vinyl ethyl ether copolymer, styrene-vinyl methyl ketone copolymer, and styrene-acrylonitrile-indene copolymer; Polyvinyl chloride, phenolic resin, natural modified phenolic resin, natural resin modified maleic acid resin, acrylic resin, methacrylic resin, polyvinyl acetate, silicone resin, polyester, polyurethane, polyamide, furan resin, epoxy resin, xylene resin, polyvinyl butyral, terpene resin, coumarone-indene resin, petroleum-based resin.

[0049] Among these, it is preferable to use polyester from the viewpoint of low-temperature fixability and chargeability of the toner.

[0050] <Various additives> If necessary, the toner may contain one or more additives selected from a colorant, a wax, a charge control agent, a developer, an external additive, etc. Various additives used in the toner will be specifically described.

[0051] <Wax> The toner particles of the present disclosure may contain a wax. Examples of the wax include the following:

[0052] Hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; Oxides of hydrocarbon waxes such as oxidized polyethylene wax or block copolymers thereof; Waxes whose main component is fatty acid esters, such as carnauba wax; Deoxidized carnauba wax and other fatty acid esters that have been partially or completely deoxidized.

[0053] Among these, from the viewpoints of low-temperature fixing property and hot offset resistance of the toner, hydrocarbon waxes such as paraffin wax and Fischer-Tropsch wax, and fatty acid ester waxes such as carnauba wax are preferred.

[0054] In the present disclosure, from the viewpoint of hot offset resistance of the toner, hydrocarbon waxes are more preferable.

[0055] The content of the wax in the toner particles is preferably 1.0 part by mass or more and 20.0 parts by mass or less with respect to 100 parts by mass of the binder resin in the toner particles. When the content of the wax is in the above range, hot offset resistance at high temperatures is further improved.

[0056] <Coloring agent> The toner particles of the toner of the present disclosure may contain a colorant. As the colorant, a known yellow colorant, magenta colorant, cyan colorant, or black colorant can be used.

[0057] Examples of black colorants include carbon black, and colorants toned to black using a yellow colorant, a magenta colorant, and a cyan colorant.

[0058] As the colorant, a pigment or a dye may be used alone, or a dye and a pigment may be used in combination.

[0059] The content of the colorant in the toner particles is preferably 0.1 parts by mass or more and 30.0 parts by mass or less with respect to 100 parts by mass of the binder resin in the toner particles.

[0060] <Magnetic material> The toner of the present disclosure may be either a magnetic toner or a non-magnetic toner, but when used as a magnetic toner, it is preferable to use magnetic iron oxide as the magnetic material contained in the toner particles. Examples of magnetic iron oxide include magnetite, maghematite, and ferrite.

[0061] The content of the magnetic material in the toner particles is preferably 25 parts by mass or more and 95 parts by mass or less, and more preferably 30 parts by mass or more and 45 parts by mass or less, relative to 100 parts by mass of the binder resin in the toner particles.

[0062] <Charge control agent> The toner particles of the toner of the present disclosure may contain a charge control agent. The charge control agent includes a negative charge control agent and a positive charge control agent.

[0063] Examples of negative charge control agents include metal salicylate compounds, metal naphthoate compounds, metal dicarboxylate compounds, polymeric compounds having sulfonic acid or carboxylic acid on the side chain, polymeric compounds having sulfonate or sulfonate ester on the side chain, polymeric compounds having carboxylate or carboxylate ester on the side chain, boron compounds, urea compounds, silicon compounds, and calixarenes.

[0064] When the toner particles contain a charge control agent, the charge control agent may be added internally or externally to the toner particles.

[0065] The content of the charge control agent in the toner particles is preferably 0.2 parts by mass or more and 10.0 parts by mass or less with respect to 100 parts by mass of the binder resin in the toner particles.

[0066] <External additive particles> The toner of the present disclosure may contain additive particles other than the toner additive particles of the present disclosure in order to improve the fluidity of the toner or adjust the triboelectric charge amount. As the inorganic fine particle additive particles, inorganic fine particles such as silicon oxide (silica), aluminum oxide (alumina), titanium oxide (titania), strontium titanate, and calcium carbonate are preferable. As the additive particles other than inorganic fine particles, for example, resin fine particles such as vinyl resin, polyester, and silicone resin can be mentioned.

[0067] These inorganic fine particles and resin fine particles function as assistants for controlling the chargeability of the toner and for improving fluidity and cleaning.

[0068] <Developer> The toner of the present disclosure may be used as a two-component developer by mixing with a magnetic carrier. As the magnetic carrier, known magnetic particles such as magnetite particles, ferrite particles, and magnetic material-dispersed resin particles can be used.

[0069] The method of coating the carrier core surface with the coating resin is not particularly limited, and can be performed by a known method. For example, there is a so-called immersion method in which the carrier core and the coating resin solution are stirred while volatilizing the solvent, and the carrier core surface is coated with the coating resin. Specific examples include a universal mixer (manufactured by Fuji Paudal Co., Ltd.) and a Nauta Mixer (manufactured by Hosokawa Micron Co., Ltd.). There is also a method in which the coating resin solution is sprayed from a spray nozzle while forming a fluidized bed, and the carrier core surface is coated with the coating resin. Specific examples include a Spira Coater (manufactured by Okada Seiko Co., Ltd.) and a Spiraflow (manufactured by Freund Corporation). There is also a method in which the coating resin is coated in a particle state on the magnetic carrier core in a dry manner. Specific examples include a treatment method using an apparatus such as a Hybridizer (manufactured by Nara Machinery Co., Ltd.), a Mechanofusion (manufactured by Hosokawa Micron Co., Ltd.), a HighFlex Gral (manufactured by Fukae Powtec Co., Ltd.), and a Theta Composer (manufactured by Tokuju Kogyo Co., Ltd.).

[0070] <Method of manufacturing toner particles> The toner particles of the present disclosure can be produced by a known method for producing toner particles, such as a melt kneading method, an emulsion aggregation method, or a solution suspension method.

[0071] The procedure for producing the toner by the pulverization method will be described below.

[0072] In the raw material mixing process, materials constituting the toner particles, such as binder resin, release agent, colorant, crystalline polyester, and other components such as charge control agent as necessary, are weighed out in predetermined amounts, blended, and mixed. Examples of mixing devices include double con mixers, V-type mixers, drum mixers, super mixers, Henschel mixers, Nauta mixers, and Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.).

[0073] Next, the mixed materials are melt-kneaded to disperse the wax in the binder resin. In the melt-kneading process, a batch-type kneader such as a pressure kneader or a Banbury mixer, or a continuous kneader can be used, and single-screw or twin-screw extruders are mainstream due to their advantage of continuous production. For example, a KTK twin-screw extruder (manufactured by Kobe Steel, Ltd.), a TEM twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.), a PCM kneader (manufactured by Ikegai Iron Works Co., Ltd.), a twin-screw extruder (manufactured by KCK Corporation), a Co-kneader (manufactured by Buss Co., Ltd.), and Kneadex (manufactured by Nippon Coke and Engineering Co., Ltd.) can be mentioned. Furthermore, the resin composition obtained by melt-kneading may be rolled with a two-roller or the like, and cooled with water or the like in a cooling process.

[0074] The cooled resin composition is then pulverized to a desired particle size in a pulverization process, which involves coarse pulverization using a pulverizer such as a crusher, hammer mill, or feather mill, followed by further pulverization using a pulverizer such as a Cryptron System (Kawasaki Heavy Industries), a Super Rotor (Nisshin Engineering), a Turbo Mill (Turbo Kogyo), or an air jet type pulverizer.

[0075] Thereafter, as necessary, the mixture is classified using a classifier or sieve such as an inertial classification type Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.), a centrifugal classification type Turboplex (manufactured by Hosokawa Micron Corporation), a TSP Separator (manufactured by Hosokawa Micron Corporation), or a Faculty (manufactured by Hosokawa Micron Corporation).

[0076] As a method for external addition treatment, for example, a method of stirring and mixing using the following mixer as an external addition device can be mentioned.

[0077] Double cone mixer, V-type mixer, drum type mixer, super mixer, Henschel mixer, Nauta mixer, Mechano Hybrid (manufactured by Nippon Coke and Engineering Co., Ltd.), Nobilta (manufactured by Hosokawa Micron Corporation), etc.

[0078] In this case, if necessary, external additive particles other than the silica fine particles, such as a fluidizing agent, may be added externally.

[0079] <Various measurement methods> <Method for measuring particle size of external additive particles> The particle size of the external additive particles can be calculated from an image of the external additive particles taken with a Hitachi ultra-high resolution field emission scanning electron microscope S-4800 (Hitachi High-Technologies Corporation). The image taking conditions for the S-4800 are as follows.

[0080] (1) Sample preparation Apply a thin layer of conductive paste to a sample stage (aluminum sample stage 15 mm x 6 mm), then spray the additive particles onto the paste. Then, use air to remove excess additive particles from the sample stage and dry thoroughly. Set the sample stage in the sample holder, and adjust the sample stage height to 36 mm using the sample height gauge.

[0081] (2) S-4800 observation condition setting The particle size is calculated using the image obtained by observing the backscattered electron image of the S-4800. Because backscattered electron images have less charge-up of particles than secondary electron images, the particle size can be measured with high accuracy. Pour liquid nitrogen into the anti-contamination trap attached to the S-4800's body until it overflows, and leave it for 30 minutes. Start the S-4800's "PC-SEM" and perform flushing (cleaning the FE chip, which is the electron source). Click the acceleration voltage display part of the control panel on the screen, press the [Flushing] button, and open the flushing execution dialog. Make sure that the flushing intensity is 2 and execute it. Make sure that the emission current by flushing is 20 to 40 μA. Insert the specimen holder into the specimen chamber of the S-4800's body. Press [Origin] on the control panel to move the specimen holder to the observation position. Click the acceleration voltage display part to open the HV setting dialog, and set the acceleration voltage to [1.1 kV] and the emission current to [20 μA]. In the [Basic] tab of the operation panel, set the signal selection to [SE], select the SE detector to [Upper (U)] and [+BSE], and select [LA100] in the selection box to the right of [+BSE] to set the mode to observation with backscattered electron images. In the [Basic] tab of the operation panel as well, set the probe current in the electron optical system condition block to [Normal], the focus mode to [UHR], and the WD to [4.5mm]. Press the [ON] button in the acceleration voltage display section of the control panel to apply the acceleration voltage.

[0082] (3) Focus adjustment Rotate the focus knob [COARSE] on the operation panel, and adjust the aperture alignment once the image is in focus to a certain extent. Click [Align] on the control panel to display the alignment dialog and select [Beam]. Rotate the STIGMA / ALIGNMENT knobs (X, Y) on the operation panel to move the displayed beam to the center of the concentric circles. Next, select [Aperture] and rotate the STIGMA / ALIGNMENT knobs (X, Y) one by one to stop the image movement or to minimize its movement. Close the aperture dialog and adjust the focus using autofocus. After that, set the magnification to 80,000 (80k)x, adjust the focus using the focus knob and STIGMA / ALIGNMENT knob as above, and then adjust the focus using autofocus again. Repeat this operation to adjust the focus. Here, if the inclination angle of the observation surface is large, the measurement accuracy of the coverage rate is likely to be low, so when adjusting the focus, select an observation surface with as little surface inclination as possible for analysis by selecting one that can simultaneously bring the entire observation surface into focus.

[0083] (4) Image storage Adjust the brightness in ABC mode, take a photo with a size of 640 x 480 pixels, and save it. Use this image file for the following analysis.

[0084] (5) Image analysis The particle size of 300 randomly selected external additive particles is measured to obtain the number-average particle size. In this disclosure, the particle size can be calculated by binarizing the image obtained by the above-mentioned method using image analysis software Image-Pro Plus ver.5.0.

[0085] <Measurement of weight average particle size (D4) of toner particles> The weight-average particle diameter (D4) of the toner particles is measured with an effective measurement channel count of 25,000 channels using a precision particle size distribution measuring device using the narrow hole electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube, and the accompanying dedicated software for setting measurement conditions and analyzing measurement data, "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.), and the measurement data is analyzed and calculated.

[0086] The aqueous electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in deionized water to a concentration of approximately 1% by mass, for example, "ISOTON II" (manufactured by Beckman Coulter).

[0087] Before performing measurements and analysis, the dedicated software is set up as follows.

[0088] In the "Change Standard Measurement Method (SOM) screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check the aperture tube flush after measurement.

[0089] In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range to 2 μm to 60 μm.

[0090] The specific measurement methods are as follows (1) to (7).

[0091] (1) Pour about 200 ml of the above electrolyte solution into a 250 ml round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "Aperture Tube Flush" function of the dedicated software to remove dirt and air bubbles from inside the aperture tube.

[0092] (2) Place about 30 ml of the above electrolyte solution in a 100 ml flat-bottom glass beaker, and add about 0.3 ml of a solution prepared by diluting "Contaminon N" (a 10% aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments made from a nonionic surfactant, anionic surfactant, and organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) three times by mass with deionized water as a dispersant.

[0093] (3) A specified amount of deionized water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two oscillators with an oscillation frequency of 50 kHz built in with a phase shift of 180 degrees and an electrical output of 120 W, and approximately 2 ml of the above-mentioned Conaminon N is added to this water tank.

[0094] (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized.

[0095] (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner particles are added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower.

[0096] (6) In the round-bottom beaker (1) placed in the sample stand, the electrolyte solution (5) in which the toner particles are dispersed is dropped using a pipette to adjust the measurement concentration to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000.

[0097] (7) Analyze the measurement data using the dedicated software attached to the device to calculate the weight-average particle size (D4). When setting the graph / volume% with the dedicated software, the "average diameter" on the analysis / volume statistical value (arithmetic mean) screen is the weight-average particle size (D4).

[0098] <Measurement of Weight-Average Molecular Weight by GPC> The molecular weight distribution of the sample is measured by gel permeation chromatography (GPC) as follows.

[0099] First, dissolve the sample in tetrahydrofuran (THF) at room temperature over 24 hours. Then, filter the resulting solution through a solvent-resistant membrane filter "Mae Shiori Disk" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. Note that the sample solution is adjusted so that the concentration of the components soluble in THF is about 0.8% by mass. Using this sample solution, perform the measurement under the following conditions. · Apparatus: HLC8120 GPC (Detector: RI) (manufactured by Tosoh Corporation) · Column: 7-series of Shodex KF-801, 802, 803, 804, 805, 806, 807 (manufactured by Showa Denko KK) · Eluent: Tetrahydrofuran (THF) · Flow rate: 1.0 ml / min · Oven temperature: 40.0 °C · Sample injection volume: 0.10 ml When calculating the molecular weight of the sample, use the molecular weight calibration curve prepared using a standard polystyrene resin (for example, product names "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500", manufactured by Tosoh Corporation).

Example

[0100] The present disclosure will be described in more detail below with reference to examples, but is not limited thereto. First, examples of production of magnetic carrier 1 and toner particles 1, and preparation of various polyrotaxanes used in each example will be described.

[0101] <Magnetic Carrier 1 Manufacturing Example> [Manufacturing example of magnetic core particle 1] Step 1 (weighing and mixing): Fe2O362.7 parts by mass MnCO329.5 parts by mass Mg(OH)26.8 parts by mass SrCO31.0 parts by mass The ferrite raw materials were weighed so as to obtain the above composition ratio, and then pulverized and mixed for 5 hours in a dry vibration mill using stainless steel beads with a diameter of 1 / 8 inch.

[0102] Step 2 (Pre-firing): The obtained pulverized material was made into pellets of about 1 mm square using a roller compactor. The pellets were passed through a vibrating sieve with 3 mm openings to remove coarse powder, and then through a vibrating sieve with 0.5 mm openings to remove fine powder. The pellets were then fired in a burner-type firing furnace at 1000°C for 4 hours in a nitrogen atmosphere (oxygen concentration 0.01% by volume) to produce calcined ferrite. The composition of the calcined ferrite obtained was as follows: (MnO)a(MgO)b(SrO)c(Fe2O3)d In the above formula, a = 0.257, b = 0.117, c = 0.007, d = 0.393

[0103] Step 3 (Crushing): After crushing to about 0.3 mm using a crusher, 30 parts by mass of water was added to 100 parts by mass of the calcined ferrite using zirconia beads with a diameter of 1 / 8 inch, and the mixture was crushed in a wet ball mill for 1 hour. The slurry was crushed for 4 hours in a wet ball mill using alumina beads with a diameter of 1 / 16 inch to obtain a ferrite slurry (finely crushed calcined ferrite).

[0104] ·Process 4 (granulation process): To the ferrite slurry, 1.0 parts by mass of ammonium polycarboxylate as a dispersant and 2.0 parts by mass of polyvinyl alcohol as a binder were added per 100 parts by mass of the calcined ferrite, and the mixture was granulated into spherical particles using a spray dryer (manufacturer: Okawara Kakoki). After adjusting the particle size of the resulting particles, the mixture was heated at 650°C for 2 hours using a rotary kiln to remove the organic components of the dispersant and binder.

[0105] Step 5 (firing): In order to control the firing atmosphere, the material was heated from room temperature to 1300°C in a nitrogen atmosphere (oxygen concentration 1.00% by volume) in an electric furnace over a period of 2 hours, and then fired at 1150°C for 4 hours. The material was then cooled to 60°C over a period of 4 hours, returned from the nitrogen atmosphere to the air, and removed at a temperature of 40°C or less.

[0106] Step 6 (sorting step): After crushing the agglomerated particles, low magnetic particles were removed by magnetic separation, and coarse particles were removed by sieving through a sieve with 250 μm openings to obtain magnetic core particles 1 having a volume distribution standard 50% particle size (D50) of 37.0 μm.

[0107] [Preparation of coating resin 1] Cyclohexyl methacrylate monomer 26.8 parts Methyl methacrylate monomer 0.2 parts Methyl methacrylate macromonomer 8.4 parts (A macromonomer with a weight-average molecular weight of 5000 and a methacryloyl group at one end) Toluene 31.3 parts Methyl ethyl ketone 31.3 parts The above materials were added to a four-necked separable flask equipped with a reflux condenser, a thermometer, a nitrogen inlet tube, and a stirrer, and nitrogen gas was introduced to create a sufficient nitrogen atmosphere, and then the flask was heated to 80°C, and 2.0 parts of azobisisobutyronitrile was added and refluxed for 5 hours to polymerize. Hexane was poured into the resulting reaction product to precipitate a copolymer, and the precipitate was filtered and then vacuum dried to obtain coating resin 1. The resulting coating resin 1 was dissolved in 30 parts by mass, 40 parts by mass of toluene, and 30 parts by mass of methyl ethyl ketone to obtain polymer solution 1 (solid content 30% by mass).

[0108] [Preparation of coating resin solution 1] Polymer solution 1 (resin solids concentration 30%) 33.3 parts Toluene 66.4 parts Carbon black (Regal 330; Cabot Corporation) 0.3 parts (Primary particle size 25nm, nitrogen adsorption specific surface area 94m2 / g, DBP oil absorption 75ml / 100g) The above materials were dispersed for 1 hour using zirconia beads with a diameter of 0.5 mm in a paint shaker. The resulting dispersion was filtered through a 5.0 μm membrane filter to obtain a coating resin solution 1.

[0109] [Resin coating process] 100 parts by mass of magnetic core particles 1 and 2.5 parts by mass of coating resin solution 1 as a resin component were added to a vacuum degassing kneader maintained at room temperature. After addition, the mixture was stirred at a rotation speed of 30 rpm for 15 minutes, and after a certain amount of the solvent (80% by mass) had evaporated, the mixture was heated to 80°C while mixing under reduced pressure, and toluene was distilled off over 2 hours, after which it was cooled. The magnetic carrier obtained was separated into low magnetic products by magnetic separation, passed through a sieve with an opening of 70 μm, and then classified with a wind classifier to obtain magnetic carrier 1 having a 50% particle size (D50) of 38.2 μm based on volume distribution.

[0110] <Production Example of Toner Particle 1> Polyester resin 1: 100.0 parts by weight [Composition (mol%) [polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane:polyoxyethylene(2.2)-2,2-bis(4-hydroxyphenyl)propane:terephthalic acid:dodecylsuccinic acid:trimellitic acid=80:20:75:10:15], Mw=152,000, Mw / Mn=32, amount of components with molecular weight of 100 to 5000=25% by mass, acid value=12 mgKOH / g] 3,5-di-t-butylsalicylic acid aluminum compound: 0.1 parts by mass Fischer-Tropsch wax (maximum endothermic peak temperature: 90°C): 5.0 parts by mass CI Pigment Blue 15:3 5.0 parts by weight The above materials were mixed in a Henschel mixer (product name: FM75J type, manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) at a rotation speed of 20 s. -1 After mixing under conditions of 1000 rpm and a rotation time of 5 minutes, the mixture was kneaded in a twin-screw kneader (product name: PCM-30, manufactured by Ikegai Corporation) set at a temperature of 125°C. The kneaded mixture was cooled and coarsely crushed to 1 mm or less using a hammer mill to obtain a coarsely crushed product. The coarsely crushed product was finely crushed using a mechanical crusher (product name: T-250, manufactured by Turbo Kogyo Co., Ltd.). Further, classification was performed using a rotary classifier (product name: 200TSP, manufactured by Hosokawa Micron Corporation) to obtain toner particles 1. The operating conditions of the rotary classifier (product name: 200TSP, manufactured by Hosokawa Micron Corporation) were a classification rotor rotation speed of 50.0 s -1 The weight average particle size (D4) of the obtained toner particles was 6.2 μm.

[0111] <Preparation of Polyrotaxane A1> The following materials were added to a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and stirred. 10.0g of the following polyrotaxane 1 (Polyrotaxane 1: SeRM Super Polymer SA1305P-20 (product name), manufactured by ASM. The chain molecule has a polyethylene glycol structure and an adamantyl group at the end of the chain molecule, and contains, as a cyclic molecule, multiple α-cyclodextrins having a polycaprolactone structure in the side chain. In addition, since the end of the side chain has an acrylic skeleton, it has a vinyl polymerizable carbon-carbon double bond.) ·1.0N-NaOH aqueous solution 40mL 1,4-Butanediol diglycidyl ether (Tokyo Chemical Industry Co., Ltd.) 1.2 mL

[0112] The mixture was stirred at 23°C for 24 hours to obtain a polyrotaxane in which the cyclic molecules were crosslinked. After isolation, 600.0g of xylene, 150.0g of styrene, 50.0g of methyl methacrylate, and 1.5g of initiator t-butyl peroxypivalate were added, and polymerization was carried out for 3 hours while rotating the stirrer at 90°C to obtain a reaction product. The reaction product was washed and dried to obtain polyrotaxane A1 in which cyclodextrins were chemically bonded to each other and side chains having a polycaprolactone structure and a styrene-methyl methacrylate polymer structure were bonded to the cyclodextrins.

[0113] <Preparation of Polyrotaxane A2> The following materials were added to a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and stirred. 10.0g of the following polyrotaxane 2 (Polyrotaxane 2: SeRM Super Polymer SM1305P-20 (product name), manufactured by ASM. The chain molecule has a polyethylene glycol structure and an adamantyl group at the end of the chain molecule, and contains, as a cyclic molecule, multiple α-cyclodextrins having a polycaprolactone structure in the side chain. In addition, since the end of the side chain has a methacryl skeleton, it has a vinyl polymerizable carbon-carbon double bond.) 40mL of 1.0N NaOH solution 1,4-Butanediol diglycidyl ether (Tokyo Chemical Industry Co., Ltd.) 1.2 mL

[0114] The mixture was stirred at 23°C for 24 hours to obtain a polyrotaxane in which the cyclic molecules were crosslinked. After isolation, 600.0g of xylene, 250.0g of styrene, 75.0g of methyl methacrylate, and 1.5g of initiator t-butyl peroxypivalate were added, and polymerization was carried out for 5 hours while rotating the stirrer at 90°C to obtain a reaction product. The reaction product was washed and dried to obtain polyrotaxane A2 in which cyclodextrin molecules were chemically bonded to each other and side chains having a polycaprolactone structure and a styrene-methyl methacrylate polymer structure were bonded to the cyclodextrin.

[0115] <Preparation of Polyrotaxane A3> The following materials were added to a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and stirred. 10.0g of the above polyrotaxane 2 ·1.0N-NaOH aqueous solution 40mL 1,4-Butanediol diglycidyl ether (Tokyo Chemical Industry Co., Ltd.) 1.2 mL

[0116] The mixture was stirred at 23°C for 24 hours to obtain a polyrotaxane in which the cyclic molecules were crosslinked. After isolation, 600.0g of xylene, 300.0g of styrene, 100.0g of methyl methacrylate, and 1.5g of initiator t-butyl peroxypivalate were added, and polymerization was carried out for 8 hours while rotating the stirrer at 90°C to obtain a reaction product. The reaction product was washed and dried to obtain polyrotaxane A3 in which cyclodextrin molecules were chemically bonded to each other and side chains having a polycaprolactone structure and a styrene-methyl methacrylate polymer structure were bonded to the cyclodextrin.

[0117] <Preparation of Polyrotaxane A4> To a reaction vessel equipped with a stirrer, condenser, and thermometer were added the following materials: Xylene 1200.0g 10.0g of the above polyrotaxane 2 Styrene 1000.0g Methyl methacrylate 350.0g t-Butyl peroxypivalate 1.5g

[0118] Next, polymerization was carried out for 24 hours while rotating the stirrer and maintaining the temperature at 90°C, obtaining a reaction product. The reaction product was washed and dried to obtain polyrotaxane A4, in which side chains having a polycaprolactone structure and a styrene-methyl methacrylate polymer structure are bonded to cyclodextrin.

[0119] <Preparation of Polyrotaxane A5> The following materials were added to a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and stirred. Xylene 1200.0g 10.0g of the above polyrotaxane 2 Styrene 1000.0g Methyl methacrylate 500.0g t-Butyl peroxypivalate 1.5g

[0120] Polymerization was carried out for 24 hours while rotating the stirrer and maintaining the temperature at 90°C, obtaining a reaction product. The reaction product was washed and dried to obtain polyrotaxane A5, in which side chains having a polycaprolactone structure and a styrene-methyl methacrylate polymer structure are bonded to cyclodextrin.

[0121] <Preparation of Polyrotaxane A6> Polyrotaxane A6 was prepared by washing and drying the above polyrotaxane 2.

[0122] <Preparation of Polyrotaxane A7> Polyrotaxane A7 was prepared by washing and drying the following polyrotaxane 3. Polyrotaxane 3: Selm Super Polymer SH1310P (product name), manufactured by ASM. The chain molecule has a polyethylene glycol structure, an adamantyl group at the end of the chain molecule, and multiple α-cyclodextrins with polycaprolactone structures in the side chains as cyclic molecules. Also, a hydroxyl group is present at the end of the side chain.

[0123] <Preparation of Polyrotaxane A8> In 100 mL of pure water, add 2,2,6,6-tetramethyl-1-piperidinedioxy radical (TEMPO) (6.4 × 10 -4 mol) was added, and the pH was adjusted to 10 to 11. The following materials were added to this solution and stirred at room temperature for 10 to 15 minutes to oxidize the ends of the polyethylene glycol. Sodium bromide 9.7×10 -4 Mol Sodium hypochlorite solution 13% by mass 10mL Polyethylene glycol (Aldrich) n=35,000 7.0×10 -4 Mol Then, 10 ml of ethanol was added, the pH was adjusted to 2, and dichloromethane extraction was performed three times using 100 ml of dichloromethane.

[0124] The dichloromethane extract was evaporated to dryness under reduced pressure, dissolved in ethanol at 40-50°C, frozen for one day and night, and then polyethylene glycol with a carboxylic acid terminal group (hereinafter referred to as PEG-COOH) was collected by centrifugation. The obtained PEG-COOH was freeze-dried.

[0125] The resulting PEG-COOH was dissolved in 8.6 × 10 -5 mol and 1.2 × 10 α-cyclodextrin -2 mol was dissolved in 100 mL of pure water and allowed to stand in a freezer overnight. The resulting white paste-like compound was then freeze-dried to obtain a powdered inclusion complex.

[0126] The following materials were dissolved in 100 mL of anhydrous dimethylformamide and reacted at 4° C. for 24 hours. Obtained inclusion complex: 14 g Adamantaneamine 1.1×10 -3 Mol Benzotriazol-1-yloxy-tris(dimethylamino)phosphonium salt 1.1×10 -3 Mol Ethylisopropylamine 1.2×10 -3 Mol Thereafter, the mixture was washed twice with a dimethylformamide / methanol solution (1:1, v / v) and methanol, and then further washed with a mixed solution of 80 mL of anhydrous dimethyl sulfoxide and 800 mL of pure water, followed by freeze-drying to obtain polyrotaxane A8 in which α-cyclodextrin was encapsulated.

[0127] <Example 1> <Production Example of External Additive Particle 1> 600.0 parts xylene Polyrotaxane A1 10.0 parts Styrene 150.0 parts Methyl methacrylate 50.0 parts Initiator: 15.0 parts t-butyl peroxypivalate

[0128] The above materials were added to a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and polymerization was carried out for 3 hours while maintaining the temperature at 90° C. with the stirrer rotating, to obtain a reaction product. The obtained reaction product was washed and dried to obtain external additive particles 1 having a particle size of 100 nm. The external additive particles 1 were particles containing the above polyrotaxane A1 (first resin) and a styrene-methyl methacrylate copolymer (second resin).

[0129] <Toner 1 Manufacturing Example> To 100.0 parts by mass of toner particles 1, 1.0 part by mass of hydrophobic silica microparticles having an average primary particle size of 15 nm and surface-treated with 20.0% by mass of hexamethyldisilazane, and 5.0 parts by mass of toner additive particles 1 were added, mixed in a Henschel mixer (product name: FM75J type, manufactured by Mitsui Miike Chemical Engineering Co., Ltd.), and passed through an ultrasonic vibration sieve with a mesh size of 54 μm to obtain toner 1.

[0130] <Example of manufacturing two-component developer> The obtained toner 1 and the above magnetic carrier 1 were mixed in a V-type mixer (product name: V-10 type, Tokuju Seisakusho Co., Ltd.) for 0.5 seconds so that the toner concentration became 9% by mass. -1and 5 minutes to obtain a two-component developer.

[0131] <Example of manufacturing replenishment developer> The obtained toner 1 and the above magnetic carrier 1 were mixed in the above V-type mixer for 0.5 seconds so that the toner concentration became 90% by mass. -1 The mixture was mixed for 5 minutes to obtain a replenishment developer.

[0132] <Evaluation> First, a modified full-color copier (product name: imagePRESS C10000VP, manufactured by Canon Inc.) was used as the image forming apparatus, and two-component developer 1 was charged into the developing device of the cyan station. The modification of the copier was to make the developing bias adjustable.

[0133] In addition, when forming an image, the developer in the cyan developing device was replaced with the above-mentioned two-component developer 1, and the developer in the cyan refill developer container was replaced with the above-mentioned refill developer 1. The reason why the two-component developer and the refill developer were used in the evaluation is that the use of both is a normal mode when using the image forming apparatus.

[0134] During the durability test in the following evaluation, the paper was passed through under the same developing and transferring conditions as the first sheet (but without calibration). The print ratio of the output image was 30%, and the developing bias was adjusted so that the initial image density was 1.55. The paper used for evaluation was A4-size plain paper for copying (product name: CF-C081, basis weight: 81.4 g / m 2 , Canon Marketing Japan) was used.

[0135] <Evaluation of image density> First, using the above device, a durability test of outputting 30,000 images was performed in a room temperature and low humidity environment (23°C / 5% RH, hereinafter referred to as N / L environment). After this durability test, three images were outputted on A3 size paper with a solid image formed on the entire surface. For the third outputted image, the density of the outputted image was measured at five points using a spectrodensitometer (product name: 500 series) manufactured by X-Rite, and the average value of the five points was taken as the image density after durability. The image density was evaluated based on the maintenance rate of the image density after durability relative to the initial image density of 1.55. The results are shown in Table 1.

[0136] It is considered that the larger the image density maintenance rate, the smaller the change in the chargeability of the toner is, and the less likely the image density is to change.

[0137] <Evaluation of image fog> First, using the above device, a durability test was performed on 30,000 images output in a high temperature and high humidity environment (30°C / 80% RH, hereinafter referred to as H / H environment). After that, 10 sheets of 00h images were output, and the average reflectance Dr (%) of the image area on the 10th sheet of paper was measured using a reflectometer (Tokyo Denshoku's "REFLECTOMETER MODEL TC-6DS"). The same measurement was also performed on the non-image area, and the average reflectance Ds (%) on the paper was measured. The above Dr (%) and Ds (%) were then substituted into the following formula to calculate the fog (%). The calculation results are shown in Table 1. Fog (%) = Dr (%) - Ds (%) It is believed that the smaller the fog (%) value, the less likely the toner charge is to be insufficient, and image fog is less likely to occur.

[0138] <Method for Evaluating Residual Toner Amount> First, a 30,000-sheet image output durability test was performed under normal temperature and humidity conditions (23°C / 50% RH, hereinafter referred to as N / N environment), and then three sheets of A3-sized paper with solid images formed on the entire surface were output. Then, a transparent polyester adhesive tape was attached to the surface of the photoconductor drum after the solid image was formed, and then peeled off. The peeled adhesive tape was attached to a piece of paper, and the image density of the adhesive tape was measured. In addition, as a blank, only the adhesive tape was attached to a piece of paper, and the image density was also measured. The value obtained by subtracting the image density of the blank from the image density of the adhesive tape peeled off from the photoconductor drum was evaluated as the density of the transfer residual toner. The evaluation results are shown in Table 1. It is considered that the smaller the value of the density, the less likely it is that the external additive particles are embedded and the toner base and the photoconductor drum are less likely to adhere to each other, and the amount of transfer residual toner is reduced.

[0139] The image density in this evaluation was measured with a spectrodensitometer (500 series, X-Rite).

[0140] <Examples 2 to 17> Toner additive particles 2 to 17 were produced in the same manner as in Example 1, except that the materials and reaction time were changed as shown in Table 1. Two-component developers and replenishment developers were then produced and evaluated in the same manner. The evaluation results are shown in Table 1. External additive particles 2 to 17 were particles having the corresponding polyrotaxane (first resin) and a styrene-methyl methacrylate copolymer (second resin).

[0141] <Comparative Examples 1 and 2> A toner was produced in the same manner as in Example 1, except that the external additive particles 1 were changed to the external additive particles shown in Table 1, and then a two-component developer and a refill developer were produced and evaluated in the same manner. The evaluation results are shown in Table 2.

[0142] <Comparative Example 3> A toner was produced in the same manner as in Example 1, except that no external additive particles were added to the toner particles, and then a two-component developer and a refill developer were produced in the same manner and evaluated. The evaluation results are shown in Table 2.

[0143] [Table 1]

[0144] In Table 1, the molecular weight of the cyclic molecule and the particle size of the external additive particles were measured by the method described above.

Claims

1. A toner additive particle containing a resin, The resin includes a first resin and a second resin different from the first resin, the first resin is a polyrotaxane; The polyrotaxane is (i) a plurality of cyclic molecules; (ii) a chain molecule that is pierced and included in the ring of the cyclic molecule; having (iii) the chain molecule has two or more blocking groups that prevent the cyclic molecule from being detached from the chain molecule; 2. A toner additive particle comprising:

2. 2. The toner external additive particle according to claim 1, wherein the cyclic molecule is a molecule having a cyclodextrin skeleton.

3. 3. The toner external additive particle according to claim 2, wherein the molecule having a cyclodextrin skeleton has a weight average molecular weight of 1,000 to 50,000.

4. 4. The toner external additive particle according to claim 2, wherein the molecule having a cyclodextrin skeleton comprises a cyclodextrin and a side chain bonded to the cyclodextrin.

5. 5. The toner external additive particle according to claim 4, wherein the side chain has a polyester structure or a vinyl polymer structure.

6. 6. The toner external additive particle according to claim 5, wherein the polyester structure is a polycaprolactone structure.

7. The particle diameter of the toner external additive particles is 50 nm or more and 300 nm or less. The toner external additive particle according to any one of claims 1 to 6.

8. 8. The toner external additive particle according to claim 1, wherein the content of the first resin is 0.1% by mass or more and 30.0% by mass or less based on the mass of the toner external additive particle.

9. the polyrotaxane comprises a first polyrotaxane and a second polyrotaxane, the polyrotaxane includes a bound polyrotaxane formed by binding the first polyrotaxane and the second polyrotaxane, The first polyrotaxane and the second polyrotaxane are bonded to each other by forming a chemical bond between a cyclic molecule of the first polyrotaxane and a cyclic molecule of the second polyrotaxane. The toner external additive particle according to any one of claims 1 to 8.

10. 10. The toner external additive particle according to claim 1, wherein the chain molecule is a molecule having a polyalkylene glycol chain.

11. A toner comprising toner particles and an external additive on the surface of the toner particles, The toner, wherein the external additive is the external toner additive particle according to any one of claims 1 to 10.

12. A two-component developer containing a toner and a magnetic carrier, A two-component developer, wherein the toner is the toner according to claim 11.

Citation Information

Patent Citations

  • Electrophotographic photoreceptor, image forming apparatus using the same, process cartridge and image forming method

    JP2011248288A

  • Electrophotographic photoreceptor and image forming device using the same

    JP2012181244A

  • Electrophotographic member

    JP2014066857A

  • Toner for electrostatic charge image development, and toner cartridge

    JP2015175964A

  • Temperature responsive polyrotaxane gel and drug carrier

    JP2017031258A